THE EFFECTIVITY OF CYSTEAMINE SUPPLEMENTATION ON IMPROVING THE IN VITRO FERTILIZATION RATE OF SHEEP OOCYTES - Nurkarimah, Dona Astari; Kaiin, Ekayanti Mulyawati; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Kedokteran Hewan, 2021)
The purpose of this study was to evaluate the effectiveness of cysteamine supplementation on the maturation medium and/or in vitro fertilization medium with regards to improving the normal fertilization rate of sheep oocytes, which are characterized by the formation of two pronuclei. Grade A and B oocytes were matured in medium-199 with 0.3% bovine serum albumin (BSA), 10 IU/mL follicle stimulating hormone (FSH), 10 IU/mL human chorionic gonadotrophin (hCG), and 50 g/mL gentamicin added for 24 hours in a 5% CO2 incubator at 39 C. The treatment group was divided into the following groups: a control group with no cysteamine (P1), a group with 100 M cysteamine in the maturation medium (P2), a group with 100 M cysteamine in the fertilization medium (P3), and a group with 100 M cysteamine both in the maturation and fertilization medium (P4). The fertilization was carried out by incubating sperm-oocytes for 12 hours and then staining them with 1% aceto-orcein to observe the formation of a pronucleus. Normal fertilization rates obtained by each treatment group were 56.5% (P1), 57.1% (P2), 57.8% (P3), and 59.9% (P4) with no significant difference (P0.05) between groups. It was concluded that 100 M cysteamine supplementation in both the maturation medium and fertilization medium was not able to increase the normal fertilization rate of sheep oocytes.